The influence of proton pump inhibitors on tissue attachment around teeth and dental implants: A scoping review - Bhavneet K. Chawla; Robert E. Cohen; Elizabeth M. Stellrecht; Lisa M. Yerke (Wiley, 2022)
Abstract Objectives Proton pump inhibitors, such as omeprazole and pantoprazole, are frequently prescribed for the treatment of acid reflux. However, those medications have been shown to affect a variety of physiologic processes, including bone homeostasis and the gastrointestinal microbiome. The objective of this study was to assess the relationship between proton pump inhibitors and attachment levels around teeth and dental implants. A scoping review was performed to assess the extent and quality of the relevant literature. Materials and Methods We used the Preferred Reporting Items for Systematic Reviews and Meta‐Analyses extension for scoping reviews (PRISMA‐ScR) and searched four relevant biomedical literature databases in addition to the grey literature. Keywords in the title and abstract fields, and subject headings for proton pump inhibitors, teeth, and dental implants were included as search terms. Results Overall search results identified 791 publications which, after applying the inclusion and exclusion criteria, yielded 27 publications that were further analyzed for relevance and quality of scientific evidence. The majority of eligible publications were retrospective cohort studies. Following critical analysis, 13 publications, including six abstracts, were used to assess the effect of proton pump inhibitors on tissue attachment around teeth and dental implants. Conclusions There are few high‐quality studies describing the effect of proton pump inhibitors on tissue attachment around teeth and dental implants. Nevertheless, among the included papers with the fewest confounding factors, there was a positive relationship between proton pump inhibitors and soft tissue attachment levels around teeth, and a predominantly negative but variable effect of proton pump inhibitors on the bone level around dental implants. Additional well‐controlled prospective studies are required to fully elucidate those relationships.